The Politics of Regulatory Change: National Forest Management Planning under Presidents Bill Clinton and George W. Bush. - Davis, Charles (Review of Policy Research, 2008)
This paper examines regulatory change from the William J. Clinton administration through the presidency of George W. Bush by focusing on their respective efforts to alter national forest planning procedures mandated by the National Forest Management Act of 1976 (NFMA). While rule making has become an important alternative pathway for making policy, the strategies used to develop a new rule may vary among presidents because of differing values and management styles. Both presidents were adept at framing the planning regulation to reflect dominant values such as preserving ecosystems (Clinton) or administrative efficiency (Bush). Between-administration differences in regulatory tactics also tended to alter the relative importance of institutional venues and, by extension, the influence exercised by differing political constituencies. Reprinted by permission of the publisher.